Speech Recognition in a Multi-speaker Environment by Using Hidden Markov Model and Mel-frequency Approach - Watada, Junzo; Hanayuki (2016 Third International Conference on Computing Measurement Control and Sensor Network (CMCSN), 2016)
The sound is a useful and versatile form of communication, where each sound have characteristics and levels of different frequency. Sound serves two basic functions for people around the world: signaling and communication. Several problems are found in sounds identifying, like pitch, velocity, and accuracy of processing voice data. The motivation of this research is to recognize and analyze human voice in a multi-speaker environment from the meeting or indirect conversation. In this research, a Hidden Markov Model approach is proposed as an emotion classifier to carry out testing phases using speech data.